Analysis of the Potential and Role of the Fisheries Subsector in the Economy in the Provinces of Sumatra - Putri, Julia; Firmansyah, Firmansyah; Ramdhani, Farhan; Pramusintho, Bagus; Magwa, Rizky Janatul; Putinur, Putinur (Universitas Islam Lamongan, 2025)
This study examines the potential and role of the fisheries sub-sector in the economy of Sumatra's provinces using Gross Regional Domestic Product (GRDP) data from 2004-2023. The analysis includes Growth Rate Percentage, Fisheries Sub-sector Contribution Percentage, Location Quotient (LQ), Sectoral Contribution Index (IKS), and Localization Index (LI). The findings indicate that the fisheries sub-sector growth rate in Sumatra ranges from 7.99% to 46.01%, averaging 22.4%. Its contribution to the agricultural sector varies from 6.20% to 67.63%, with an average of 20.81%, while its share of total GRDP is between 1.69% and 6.53%, averaging 3.75%. The LQ values range from 0.56 to 2.17, with an average of 1.24, indicating that this sub-sector is a base industry with production exceeding local consumption. However, the IKS values (0.02-0.07, averaging 0.04) suggest that the fisheries sub-sector is not yet a key sector. The LI values (0.01-0.09, averaging 0.03) reflect a relatively balanced distribution across Sumatra. Overall, the fisheries sub-sector contributes significantly to regional and national economic growth. However, the low IKS value indicates that its potential remains underutilized. To maximize this potential and enhance export competitiveness, strategic support through innovative policies, infrastructure investment, and modern technology adoption is essential.